The holy spirit in the New Testament - Carroll, John T., 1954- (Nashville Abingdon Press, 2018)
In an are od study that is sometimes neglected and often debated, this book offers readers fresh insight through careful attention to the different ways the New Testament writings present and interpret the spirit of God. With Caroll's guidance, readers will gain a sense of the identity and activity of the spirit manifest in the cultures and literature that informed the New Testament and its earliest audiences the author also maps the distinctive views of the holy spirit in the New Testament books, employing literary " closed reading" of texts where the spirit figures prominently. Readers discover that for the writers of the New Testament all of life is touched by the holy spirit. And for human beings this life is lived in the awareness God's presence, sustained in hope through adversity and pain, open to change and new possibilities and equipped and empowered to act boldly and speak prophetically by wise spirit shaped discernment the spirit in the New Testament is a creative force sustaining, fostering and restoring life--the first and last word both whispered and even shouted as the divine breath animating embedded and embodied human life and community.
Includes bibliographical references and index
Keywords: Bible -- New Testament -- Theology; Bible -- New Testament -- Criticism, interpretation, etc; Bible -- New testament; Holy Spirit (Judaism); Holy Spirit -- Biblical teaching; Theology